Spectrophotometric determination of Zn (II) by formation of the Zn-Orotic Acid complex - Capitán, F.; Arrebola, A. (Ars Pharmaceutica (Internet), 1966)
The influence of the pH of the medium on the absorption curves of the orotic-Zn (II) complex is studied, observing in them the existence of an isobestic point at a wavelength of 290 millimicres for pH values comprised between at least 6.25 and 9.5. The stability over time of the ornithic complex-Zn (II) is also studied, observing that it has stability for at least 4 hours.The complex complies with the law of Lambert-Beer although the slope of the corresponding straight line is significantly influenced by the concentration of orotic acid used.A method for the determination of Zn (II) in the concentration range between 0 and 49 ppm is proposed, establishing the error and its reproducibility.It is established by the spectrophotometric methods of Job, Harvey and Manning and Yoe and Jones the stoichiometry of the complex at pH 8 which turns out to be 1: 1. If we compare the results obtained in our previous work with those summarized in it, we conclude that the behavior of the orotic acid as a reagent for the spectrophotometric determination of Cu (II), Co (II) and Zn (II ) is very similar, similarly the results obtained by the corresponding described methods and even the stoichiometry of the complexes formed by the spectrophotometric methods are similar.